Applying problem-based learning to entrepreneurship education and innovation through an online laboratory - Ninik Sudarwati; Chalimah Chalimah; Dies Nurhayati (Universitas Sebelas Maret, 2024)
The research is essential to be conducted as the shift from traditional classroom instruction to online instruction becomes a requirement for 21st-century environmental learning. Before implementing e-learning, everything must be ready, and students’ attitudes must be taken into account. This study, therefore, sought to describe students' attitudes regarding online learning in entrepreneurship courses following the implementation of problem-based learning through online laboratory entrepreneurship (PBL-OLE). The research design applied is combination of quantitative and qualitative. The analysis of the data was done with quantitative descriptive techniques. The phenomenon of students' attitudes toward e-learning was documented in a number of contexts, including the TelRA domain and students' attitudes toward economic learning. The results of the student surveys were compared and explained in this descriptive quantitative study. According to the students' attitudes toward entrepreneurship, e-learning, and gender, students' perspectives were described. 28 college students who were chosen at random from University of PGRI Jombang in economic education program in East Java, Indonesia, participated in this study as respondents. Based on the E-learning challenges, the results revealed that the mean score was. Educational Institutions must be conscientious in order to produce creative classroom instruction if it wants to increase and improve students' attitudes with regard to e-learning and business.